Analysis of the Effect of Capital Structure and Profitability on Firm Value in Manufacturing Companies - Ferdinant Nuru; Subur Harahap; Noer Aisyah Barlian; Karnawi Kamar (Institut Bisnis dan Informatika Kesatuan, 2025)
In recent years, the dynamics of corporate finance have been significantly shaped by global economic volatility, technological advancements, and increasing financial market integration, especially in emerging economies. Manufacturing companies, being capital-intensive, are particularly sensitive to changes in capital structure and profitability, which serve as critical factors influencing firm value. This study investigates how capital structure and profitability affect the valuation of manufacturing firms listed on the Indonesia Stock Exchange. Employing a quantitative research design, panel data regression was applied to a purposive sample of 45 companies over the 2018–2022 period. Both fixed and random effects models were evaluated, with the Hausman test guiding model selection. Findings indicate that profitability has a robust positive impact on firm value, supporting signaling theory by demonstrating that higher profits communicate strong operational performance to investors. Conversely, higher leverage, as measured by capital structure, negatively impacts firm value, reflecting investor concerns over increased financial risk. The results suggest that firms can enhance market valuation by improving profitability, while careful management of debt levels is essential to avoid value erosion. These insights offer actionable recommendations for managers in emerging markets to optimize financial strategies and strengthen investor confidence.